Institutional support in managerial capacity building and Ghanaian SMEs growth : the mediating effect of marketing orientation - Bayu Taufiq Possumah,; Michael Karikari Appiah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study examined the effect of institutional support in managerial capacity building on marketing orientation and Small and Medium Enterprises (SME) growth. The study employed positivist research paradigm which necessitated the use of survey method. The study sample consisted of 147 participants across the Ghanaian SMEs sector. The study conterminously employed Structural Equation Modelling (SEM) and Smart-Partial Least Square (PLS) to analyze the survey questionnaire data and test the research hypotheses. The study found that institutional support in managerial capacity building had positive and significant impact on SMEs comparative advantage and performance. The study further revealed that marketing orientation has significant on SMEs growth. On contrary, the study found that institutional support in managerial capacity building has insignificant effect on marketing orientation. These results imply that continue investment and support in managerial capacity building and marketing intelligence are required to enhance SMEs growth. We suggest replication of this study in other Sub-Sahara countries since this was limited to only Ghanaian SMEs.